2013
DOI: 10.1007/s10571-013-9931-x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Transient Receptor Potential Conical Channel (TRPC)-3 Activation Induces Vasogenic Edema Formation in the Rat Piriform Cortex Following Status Epilepticus

Abstract: Transient receptor potential canonical channel (TRPC) is a nonselective cation channel permeable to Ca(2+), which express in many cell types, including neurons. However the alterations in TRPC receptor expressions in response to status epilepticus (SE) have not been explored. Therefore, the present study was designated to elucidate the roles of TRPC3 in neuronal death and vasogenic edema within the rat piriform cortex (PC) following SE. In non-SE animals, TRPC3 immunoreactivity was abundantly detected in the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Regarding TRPA1 and TRPC3 not likely described in glioma, some studies highlighted their involvement in other brain vasculature diseases, exerting a protective role against ischemic damage, controlling vasodilation in brain endothelial cells (Sullivan et al, 2016;Pires and Earley, 2018). TRPC3, when overexpressed, would lead to an increase in the BBB permeability, leading to vasogenic edema formation (Ryu et al, 2013).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Regarding TRPA1 and TRPC3 not likely described in glioma, some studies highlighted their involvement in other brain vasculature diseases, exerting a protective role against ischemic damage, controlling vasodilation in brain endothelial cells (Sullivan et al, 2016;Pires and Earley, 2018). TRPC3, when overexpressed, would lead to an increase in the BBB permeability, leading to vasogenic edema formation (Ryu et al, 2013).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The canonical transient receptor potential 3 (TRPC3) channel has been increasingly implicated in SE [12][13][14] , and we recently reported that TRPC3 channels enhance seizure intensity 15 . TRPC3 channels are non-selective cation channels known primarily for their importance in regulating intracellular calcium.…”
mentioning
confidence: 99%
“…For instance, TRPC1 and TRPC4 mediate thrombin-induced permeability increase in HUVEC monolayers (Paria et al, 2006) and mouse lung vasculature (Tiruppathi et al, 2002), respectively. Likewise, TRPC3 overexpression/hyperactivation has been associated to the exaggerated increase in blood-brain barrier (BBB) permeability observed in response to status epilepticus (Ryu et al, 2013). Furthermore, TRPM2 mediates H 2 O 2 -induced endothelial hyperpermeability in human pulmonary artery endothelial cells (Hecquet et al, 2008), whereas TRPC6 sustains endotoxin-induced disruption of pulmonary vascular barrier (Tauseef et al, 2012) and pulmonary ischemia-reperfusion evoked edema (Weissmann et al, 2012) in mice.…”
Section: Trp Channels Regulate Multiple Endothelial Cell Functionsmentioning
confidence: 99%